PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA GRAFIS TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI POKOK SEGIEMPAT DI KELAS VII MTS NEGERI MODEL PADANGSIDIMPUAN - Hilda, Lelya; Sihotang, Aulia Isma Yuni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
This research is motivated by the low of mathematics learning result of student in class VII MTs Negeri Model Padangsidimpuan caused in learning process of teacher not yet able to attract student attention, student enthusiasm in following lesson so that student have difficulties in answer mathematical problems especially in building rectangle which causes student learning outcomes have not been maximized. This research was conducted with the aim to know the influence of cooperative learning model type make a match berbantuan graphic media to the students' mathematics learning outcomes on the subject matter of quadrilateral in class VII MTs Negeri Model Padangsidimpuan. This research refers to Piaget's developmental theory which states that learning is a process whereby children actively build systems of meaning and understanding of reality through their experiences and interactions.Â This research is a quantitative research with quasi experimental method using model Pretest-Posttest Control Design Group. The population of this study is the total of students of class VII MTs Negeri Model Padangsidimpuan consisting of 11 classes totaling 418 students. The sample in this research is taken with cluster sampling technique that is 76 students. The samples in the experimental group treated 38 students and the control group were not treated 38 students. Data processing and data analysis is done by using T-Test formula.Â Based on the normality test and homogeneity test both classes are normal and homogeneous distributed. T test-test obtained by hypothesis test result that show thitung ttabel that is 4,636 1,993. H1 accepted, meaning there is a significant influence between the use of cooperative learning model type Make A Match assisted graphics media on student learning outcomes on the subject of quadrilateral in class VII MTs Negeri Model Padangsidimpuan.